2015
DOI: 10.2109/jcersj2.123.394
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetically separable MnFe<sub>2</sub>O<sub>4</sub> nanocrystals via salt-assisted solution combustion method and their utilization as dye adsorbent

Abstract: MnFe 2 O 4 nanocrystals with spinel structure were prepared by conventional solution combustion synthesis and salt-assisted solution combustion synthesis, respectively, and their adsorption capacities for Congo red (CR) were also investigated. The results showed that the MnFe 2 O 4 nanocrystals prepared with KCl salt (K-MFO) exhibited much better adsorption capacity for CR than those prepared without KCl (MFO), because the introduction of KCl into the solution combustion synthesis process results in an obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…MnFe2O4 belongs to the inverse spinel ferrites where Mn +2 ions occupy the octahedral sites of lattice structure and half of the Fe +3 cations occupy octahedral sites and the other half stay at the tetrahedral sites of a fcc lattice formed by the oxygen ions and is a wellknown soft ferrite which has been used in various technological applications such as magnetic materials, gas sensors, biomedical tools and absorbent material for hot gas, among others (Stoia et al, 2015). Several methods have been developed to synthesize MnFe2O4 nanoparticles (Mishra et al, 2006), such as solid-phase reactions, mechanical ball-milling (Chen et al, 2013), thermal decomposition (Gabal and Ata-Allah, 2004), hydrothermal method (Hou et al, 2010), coprecipitation (Amighian et al, 2006), combustion (Zhong et al, 2015), microemulsion (Scano et al, 2011) and sol-gel autocombustion (Figure 21) (Shafiu et al, 2013, Shanmugavel et al, 2014. It was reported that at elevated temperatures, MnFe2O4 is unstable in air and Mn 2+…”
Section: Mnfe2o4mentioning
confidence: 99%
“…MnFe2O4 belongs to the inverse spinel ferrites where Mn +2 ions occupy the octahedral sites of lattice structure and half of the Fe +3 cations occupy octahedral sites and the other half stay at the tetrahedral sites of a fcc lattice formed by the oxygen ions and is a wellknown soft ferrite which has been used in various technological applications such as magnetic materials, gas sensors, biomedical tools and absorbent material for hot gas, among others (Stoia et al, 2015). Several methods have been developed to synthesize MnFe2O4 nanoparticles (Mishra et al, 2006), such as solid-phase reactions, mechanical ball-milling (Chen et al, 2013), thermal decomposition (Gabal and Ata-Allah, 2004), hydrothermal method (Hou et al, 2010), coprecipitation (Amighian et al, 2006), combustion (Zhong et al, 2015), microemulsion (Scano et al, 2011) and sol-gel autocombustion (Figure 21) (Shafiu et al, 2013, Shanmugavel et al, 2014. It was reported that at elevated temperatures, MnFe2O4 is unstable in air and Mn 2+…”
Section: Mnfe2o4mentioning
confidence: 99%
“…This feature, coupled with the low cost, non-toxicity and applicability of this nanoparticle has led to a special application in adsorption. 12,13 Coupling of this nanoparticle with TiO 2 has been reported in the various sources to facilitate the adsorption and transport of nanoparticles. Besides simplifying the process, it increases the amount of adsorption due to the presence of free electrons in the TiO 2 compound.…”
Section: Introductionmentioning
confidence: 99%